Implementation of Digital-based Financial Inclusion for Millennials within the Society 5.0 Era: Implementation of Digital-based Financial Inclusion for Millenials Within the Society 5.0 Era - Faujiah, Nurul; Damayanty , Alfina (UMBanjarmasin, 2022)
The ever-evolving era, followed by increasingly sophisticated technological advances, encourages people to innovate and continue to develop existing products. This article describes the use of digital-based financial inclusion for millennials in the era of